The dynamic developmental process of adolescent non-suicidal self-injury disclosure: a qualitative study - Liu, Zikang; Wang, Ruofei; Li, Xingxue; Yuan, Zhe; Wu, Tong; Liang, Hong (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury poses a serious threat to adolescents’ mental health, and if such behavior remains unexpressed or unshared over a long period, it may lead to further deterioration of their psychological well-being. The public lacks a comprehensive understanding of the ways in which adolescents express non-suicidal self-injury.MethodsGuided by the principle of intensity sampling, this study selected cases with high information richness and intensity through snowball sampling, referral sampling, and opportunistic sampling methods. Seventeen adolescents meeting the DSM-5 criteria for non-suicidal self-injury were recruited from psychiatric outpatient clinics as study participants. Using a grounded theory approach based on in-depth interviews, a theoretical model of adolescent non-suicidal self-injury disclosure behaviors was gradually constructed.ResultsA total of 132 concepts, 51 categories, 23 subcategories, and 7 core categories were identified in this study. The core categories in the dynamic developmental process of adolescent non-suicidal self-injury disclosure include shame, emotional experience, feedback response, outcome adjustment, disclosure motivation and expectation, disclosure behavior, and contextual factors. Centered on the core category of “the dynamic developmental process of adolescent non-suicidal self-injury disclosure,” a four-stage theoretical model of dynamic adaptation in adolescent non-suicidal self-injury disclosure was constructed. This model, starting from shame and situational triggering events, delineates a four-stage dynamic process of adolescent non-suicidal self-injury disclosure: in the situational trigger stage, shame suppresses the willingness to disclose; during the disclosure decision-making stage, adolescents weigh disclosure motives against expectations and emotional experiences, generating disclosure conflicts; in the disclosure action stage, adolescents select specific methods and targets for NSSI disclosure, receiving varying feedback; and in the adjustment and adaptation stage, positive feedback promotes help-seeking, whereas negative feedback reinforces avoidance.ConclusionsThe dynamic four-stage theoretical model of adolescent non-suicidal self-injury disclosure developed in this study clearly delineates the stage-specific, cyclical, and feedback-driven characteristics of NSSI disclosure. This model innovatively reveals how adolescents continuously navigate psychological trade-offs and adjust their behaviors between shame, situational triggers, disclosure motives, and emotional experiences during the NSSI disclosure process, offering a novel theoretical perspective for understanding NSSI disclosure. Simultaneously, this model can be applied to design personalized support strategies for different stages of self-injury disclosure, enhance the effectiveness of psychological interventions, and reduce the risk of adolescent self-injury.